The relative supernovae contribution to the chemical enrichment history of Abell 1837 - Erdim, M. K.; Ezer, C.; Unver, O.; Hazar, F.; Hudaverdi, M. (OXFORD UNIV PRESS, 2021)
In this paper, we report the relative supernovae (SNe) contribution to the metal budget of the intracluster medium (ICM) of the Abell 1837 galaxy cluster at redshift z = 0.069. For this purpose, we analysed the hot ICM of the cluster and obtained radial metal distributions using XMM-Newton archival data with a total exposure of similar to 100 ks. These metal measurements consist of Mg, Si, S, Fe and Ni within a radius of 0.7 R-500, which is divided into three concentric annuli. In order to explain the observed metal abundance pattern in terms of relative supernova contributions, we used our newly developed code SNeRATIO, which utilizes theoretical nucleosynthesis models. This study covers the most recent 3D Type Ia SN and core-collapse SN yield tables. All combinations of these theoretical yields were fitted with our measured abundance ratios, and statistically acceptable ones were selected. Each of these models was found to predict a uniform SNIa percentage contribution to the total SNe from the cluster centre to the outskirts and to form an SNIa ratio distribution with a mean of 39 +/- 14. This uniformity is consistent with the early enrichment scenario, which assumes that metal production processes begin in the early phase of cluster formation, namely the proto-cluster phase at epoch z >= 2.
Keywords: supernovae: general; galaxies: clusters: intracluster medium; galaxies: clusters: individual: Abell 1837; X-rays: galaxies: clusters; INTRA-CLUSTER MEDIUM; ABUNDANCE PROFILES; PERSEUS CLUSTER; GALAXY CLUSTERS; HOT GAS; ELEMENTAL ABUNDANCES; INTRACLUSTER MEDIUM; CHANDRA OBSERVATION; RAY; MODELS; Astronomy & Astrophysics